Hubungan antara Dukungan Keluarga dengan Kemampuan Pragmatik Anak Autism Spectrum Disorder (ASD) di Kota Sragen - Indriyani, Ariesta; Aditya Setyawan, Dodiet; Abida, Liza Laela (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background: One that plays a role in the development of children's language is the family, because the family is the first environment where the child gets the first experience that will affect his life in the future. Pragmatic development is obtained by interacting with the environment around the child and through stimuli provided by the surrounding people using various methods carried out in a family or community. One of them is inviting children to interact from an early age, is a pragmatic learning method that is practiced by all parents. One of the factors that influence the development of pragmatics is social interaction. Objective: This study aims to determine the relationship between the relationship between family support and the pragmatic abilities of ASD children in Sragen. Methods: This type of quantitative research with a cross sectional design. The data collection technique uses total sampling with a sample of 30 respondents. The collected data will be analyzed univariately and bivariately using the Spearman's Rank statistical test. Results: Based on the analysis test results with Spearma's Rank, the value of ρ (sig.) is 0.001 or the value of ρ (sig.) ≤ 0.05, then Ha (alternative hypothesis) is accepted, thus indicating that there is a relationship between family support and the pragmatic ability of ASD children in Sragen city. The correlation coefficient value is 0.557, which means that the level of correlation or relationship between the two variables is in the range 0.4 to ≤ 0.6, which is the medium category. Conclusion: There is a relationship between family support and the pragmatic abilities of ASD children in Sragen City. Keywords: Family Support, Pragmatic Ability, ASD Children